The Effect Of Addressing Attention and Product Prices On The Purchase Decision Of Fashion Products On The Tiktok Shop Features In The Tiktok Application (Study on Students in Medan City) - Selin Sandrina; Nana Dyki Dirbawanto (Journal Boas : Business, Economics, Accounting And Management, 2022)
This study aims to examine the effect of advertising attractiveness on purchasing decisions for fashion products on students who use the Tiktok Shop feature on the Tiktok application, analyze the effect of product prices on purchasing decisions for fashion products on students who use the Tiktok Shop feature on the Tiktok application, and analyze the effect of advertising attractiveness and product prices simultaneously on purchasing decisions for fashion products for students using the TikTok Shop feature on the Tiktok application in the city of Medan. The research method used in this research is quantitative. The population in this study were all students using the TikTok Shop feature on the Tiktok application in the city of Medan. The sample of this study was selected using a non-probability sampling technique with a total sample of 100 respondents. Data collection techniques in this study used primary data obtained from the distribution of Google form questionnaires, and secondary data obtained from books and articles as well as previous research related to this research. The data analysis method used is validity test, reliability test, classical assumption test, multiple linear analysis, partial test, simultaneous test and determination test. TThe results of this study indicate that the attractiveness of advertising (X1) and product prices (X2) have a significant effect on purchasing decisions. The attractiveness of advertising and product prices also has a significant simultaneous effect on purchasing decisions (Y). The results of this study indicate that the attractiveness of advertising (X1) and product prices (X2) have a significant effect on purchasing decisions. The attractiveness of advertising and product prices also has a significant simultaneous effect on purchasing decisions (Y).